Advances and trends in engineering sciences and technologies : proceedings of the International Conference on Engineering Sciences and Technologies, Tatranská Štrba, High Tatras Mountains, Slovakia, 27-29 May 2015 /: proceedings of the International Conference on Engineering Sciences and Technologies, Tatranská Štrba, High Tatras Mountains, Slovakia, 27-29 May 2015. ([2016]) - Unknown
No abstract available